How dairy food affects prostate cancer - a literature overview - Bentkowska, Zuzanna; Bogoń, Aleksandra; Urbańska, Karolina; Serkis, Barbara; Miazga, Małgorzata; Celichowska, Magdalena; Golemo, Jagna; Dębińska, Julia; Ostojska, Magdalena; Górska, Magdalena (Quality in Sport, 2024)
Introduction: Prostate cancer is one of the most common type of tumors. Potential factors influencing this neoplasm are subject of many scientific studies as a scarce number of risk variables have been well-established so far. Purpose of the work: The objective of this review is to collect and interpret recent findings regarding dairy food and its influence on prostate cancer. Materials and method: A systematic research was conducted using the PubMed database. Articles in English published from 2015 to 2024 were selected using keywords: dairy products, dairy, milk, prostate cancer. State of knowledge: There is an overall positive association between total dairy products, milk and prostate cancer risk. Although whole milk is not considered as a risk factor, it has been reported that high-fat milk has a positive association with fatality rate and recurrence. Several studies presented a new potential pathomechanisms of dairy’s influence on prostate tumors. Casein, IGF-1 and exosomes are labeled as mediators between high dairy food intake and prostate cancer occurrence. Summary: As of now, there is not strong enough evidence to limit dairy food intake in the whole population. Further research is needed to explore the relationship between dairy consumption and prostate cancer. Men with diagnosed prostate tumors are suggested to eat food according to the Mediterranean diet as it has been reported that it decreases cancer-specific and overall mortality.